2015
DOI: 10.5812/asjsm.6(2)2015.24392
|View full text |Cite
|
Sign up to set email alerts
|

How the Iranian Football Coaches and Players Know About Doping?

Abstract: Background:Nowadays, doping is an intricate dilemma. Football is the nationally popular sport in Iran. On the other hand, doping is a serious health hazard sport faces today. Studies dealing with athletes’ knowledge, attitudes and behavior concerning doping in football are scarce.Objectives:Therefore, we aimed to investigate the knowledge and attitudes toward doping among the football coaches and players.Patients and Methods:In a cross sectional study, 375 participants (239 football players and 136 coaches) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
9
1
2
Order By: Relevance
“…The results of our study show that the physician was seen as the most frequently consulted (%84.6) and reliable (96.5%, neutral and more) source of doping knowledge by the athletes. Our findings are in contradiction with previous studies on French high school athletes and Iranian athletes, who declared their peers and coaches to be the primary sources about doping (Seif Barghi, Halabchi, Dvorak, & Hosseinnejad, 2015;Backhouse, Kenna, Robinson, & Atkin, 2007). It is important to note that physicians have the potential to influence athletes with regards to doping information.…”
contrasting
confidence: 99%
“…The results of our study show that the physician was seen as the most frequently consulted (%84.6) and reliable (96.5%, neutral and more) source of doping knowledge by the athletes. Our findings are in contradiction with previous studies on French high school athletes and Iranian athletes, who declared their peers and coaches to be the primary sources about doping (Seif Barghi, Halabchi, Dvorak, & Hosseinnejad, 2015;Backhouse, Kenna, Robinson, & Atkin, 2007). It is important to note that physicians have the potential to influence athletes with regards to doping information.…”
contrasting
confidence: 99%
“…Algunas investigaciones que centran su interés en examinar los conocimientos, las actitudes y las creencias de los profesionales médicos, 59 los patrocinadores 60 y los entrenadores, 61,62 reconocen algunas alternativas para promover el desarrollo de actitudes antidopaje. 63 De hecho, determinar el tipo de compromisos teóricos de los programas de investigación relacionados con el dopaje deportivo, se ha convertido en un objetivo prioritario a la hora de reconocer las concepciones, representaciones, percepciones e ideas que construyen atletas, entrenadores y médicos frente al dopaje.…”
Section: Resultados Y Análisisunclassified
“…They cautioned them about doping and its consequences. A study also reported that their respondents were concerned about the safety of supplements, although a considerable number of them considered it to be essential for success in international arena [33]. Most young athletes in a Canadian study [34] were reported to be consuming vitamin and mineral supplements only.…”
Section: Discussionmentioning
confidence: 99%